2006
DOI: 10.3354/dao071201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental salinity on sea lice Lepeophtheirus salmonis settlement success

Abstract: The sea louse Lepeophtheirus salmonis (Krøyer, 1837) (Copepoda: Caligidae) is an ectoparasite of salmonid fish. It has earlier been proposed that the free-swimming infectious copepodid stage of L. salmonis gather at river mouths to infect wild Atlantic salmon Salmo salar L. and sea trout S. trutta L. smolts during their seaward migration. This study used aquarium-based methods to investigate the survival, infective ability and behaviour of L. salmonis copepodids exposed to short periods of low salinity levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 29 publications
4
162
2
Order By: Relevance
“…The relationship between host density and infection intensity appears to depend on the transmission mode of the parasite (Côté & Poulin 1995). Sea lice copepodids are mobile crustaceans (Pike & Wadsworth 1999, Bricknell et al 2006, which actively seek their host and display a range of hostfinding behaviours when they detect host-related cues (Heuch et al 2007, Mordue Luntz & Birkett 2009). Mobile parasites searching for a host are analogous to predators seeking their prey, and similarly the probability of an individual host being 'attacked' 85 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between host density and infection intensity appears to depend on the transmission mode of the parasite (Côté & Poulin 1995). Sea lice copepodids are mobile crustaceans (Pike & Wadsworth 1999, Bricknell et al 2006, which actively seek their host and display a range of hostfinding behaviours when they detect host-related cues (Heuch et al 2007, Mordue Luntz & Birkett 2009). Mobile parasites searching for a host are analogous to predators seeking their prey, and similarly the probability of an individual host being 'attacked' 85 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Copepodids, the mobile infective stage of L. salmonis, can alter their position in the water column in response to environmental variables (Heuch et al 1995, Tucker et al 2000, Bricknell et al 2006) and actively seek their host (Heuch et al 2007, Mordue Luntz & Birkett 2009). As mobile parasites, an increase in host density could result in a lower infection intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to lice on fishes in sea cages, lice on wild and feral salmon may not be exposed to low salinities for long enough to affect their abundance until the fishes migrate into freshwater. Experiments in the laboratory and sea pens have shown that L. salmonis copepodites swim upwards towards light and do not cross into low salinity waters (Heuch 1995;Heuch et al 1995;Bricknell et al 2006). Plankton sampling discovered higher densities of L. salmonis copepodites in very shallow water along the seashore and in estuarine areas of Ireland and Scotland (Costelloe et al 1995(Costelloe et al , 1998McKibben & Hay 2004).…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…CCA indicated that the intensity of C. serratus was positively influenced by water salinity and, to some extent, by host size. Experimental studies by Bricknell et al (2006) on the caligid L. salmonis indicate that both survival and host infectivity are severely compromised by short-term exposure to reduced salinity levels. Also, water temperature has been shown to be positively associated with the development of other Caligus species such as C. elongatus and C. rogercresseyi Gonzá lez and Carvajal, 2003;Costello, 2006).…”
Section: Seasonal Changes In Prevalence and Mean Intensitymentioning
confidence: 99%